Tumor Cell‐Intrinsic CD96 Mediates Chemoresistance and Cancer Stemness by Regulating Mitochondrial Fatty Acid β‐Oxidation. Issue 7 (29th December 2022) - Li, Jiang; Xia, Qidong; Di, Can; Li, Chunni; Si, Hang; Zhou, Boxuan; Yu, Shubin; Li, Yihong; Huang, Jingying; Lu, Yiwen; Huang, Min; Liang, Huixin; et al.
Abstract: Targeting CD96 that originates in immune cells has shown potential for cancer therapy. However, the role of intrinsic CD96 in solid tumor cells remains unknown. Here, it is found that CD96 is frequently expressed in tumor cells from clinical breast cancer samples and is correlated with poor long‐term prognosis in these patients. The CD96 + cancer cell subpopulations exhibit features of both breast cancer stem cells and chemoresistance. In vivo inhibition of cancer cell‐intrinsic CD96 enhances the chemotherapeutic response in a patient‐derived tumor xenograft model. Mechanistically, CD96 enhances mitochondrial fatty acid β ‐oxidation via the CD155‐CD96‐Src‐Stat3‐Opa1 pathway, which subsequently promotes chemoresistance in breast cancer stem cells. A previously unknown role is identified for tumor cell‐intrinsic CD96 and an attractive target in improving the chemotherapeutic response. Abstract : CD96 expressed in tumor cells is correlated with poor long‐term prognosis in breast cancer patients. The CD96 + cancer cell subpopulations exhibit features of both stemness and chemoresistance. Mechanistically, CD96 enhances mitochondrial fatty acid β ‐oxidation via the CD155‐CD96‐Src‐Stat3‐Opa1 pathway, which subsequently promotes chemoresistance in breast cancer stem cells.